Emas dalam Budaya Batak - Nenggih Susilowati (Berkala Arkeologi Sangkhakala, 2012)
AbstractGolden artifacts have different varieties and decorative patterns, such as in jewellery. The presence of golden artifacts in the past is known presently from the Dutch old record in North Sumatra. At that time, the Bataknese lived an old belief of the ancestor spirits or called the megalithic tradition. The development of gold craftsmanship is seen through the golden artifacts with the typical Batak patterns influenced by the old faith as well as external decorative patterns. The proposed question is how the golden artifacts were integrated into the Bataknese culture. The study aims at collecting more knowledge of the importance of golden artifacts in Bataknese life as well as the cultural aspects reflected on those artifacts. Explorative-descriptive writing method with inductive reasoning is used to get an answer to the problem being proposed. Inductive reasoning begins at the study of data that can give a general conclusion or empirical generalization after data analysis stage process. Golden artifacts are just like pieces of art that bear a unique function in the society as well as describing such social, cultural, and religious aspects of the Bataknese in the ancient North Sumatra.AbstrakArtefak emas cukup beragam jenis dan pola hiasnya, di antaranya digunakan sebagai perhiasan. Tentang artefak emas di masa lalu diketahui melalui catatan lama ketika Belanda masuk ke wilayah Sumatera Utara. Pada masa itu etnis Batak pada umumnya masih hidup dalam kepercayaan lama yang berkaitan dengan roh nenek moyang atau dikenal dengan tradisi megalitik. Perkembangan seni kriya emas terlihat melalui artefak emas dengan pola hias khas Batak yang mendapat pengaruh religi lama, dan pola hias yang mendapat pengaruh dari luar. Permasalahannya adalah bagaimana artefak emas menjadi bagian dalam budaya masyarakat Batak ? Tulisan ini bertujuan untuk menambah pengetahuan mengenai pentingnya artefak emas dalam kehidupan masyarakat Batak serta aspek-aspek kebudayaan yang tercermin melalui artefak tersebut. Untuk dapat menjawab permasalahan yang diajukan, maka metode penulisan bertipe eksploratif- deskriptif menggunakan alur penalaran induktif. Penalaran induktif berawal dari kajian terhadap data yang dapat memberikan suatu kesimpulan yang bersifat umum atau generalisasi empiris setelah melalui proses tahap analisis data. Seperti hasil karya seni lain, artefak emas mempunyai fungsi dalam kehidupan masyarakat serta menggambarkan aspek sosial, budaya, dan religi masyarakat Batak di Sumatera Utara di masa lalu.